A Time to Plot, A Time to Reap: Coups, Regime Changes, and Inequality. Issue 8 (17th November 2022) - Bjørnskov, Christian; Knoll, Bodo; Rode, Martin
ABSTRACT: A vast economic literature examines the welfare gains and distributional consequences of economic reforms, while much less is generally known on the relationship of inequality and forced regime changes. Some studies analyze how economic inequality impacts the likelihood of coups, but the distributional outcomes of such events have been largely ignored to date. Employing novel data, we find that successful coups have a significant positive impact on the consumption shares of the lowest quintile and a strong negative impact on the highest quintile, as compared to the inexistent redistribution that results from failed coups. In addition, the redistributive effect is stronger for military coups, as compared to civilian coups, and effects seem to be substantially driven by coups against democratic regimes. Despite their negative impact on overall growth and per capita income, our results show that forced regime changes, as compared to non-successful attempts, reduce inequality at a short notice. This may partially explain their continued popularity in highly unequal developing countries.